Analisis Keefektifan Kinerja Kelompok Tani Ubikayu Varietas Lokal Nuabosi Di Desa Randotonda Kabupaten Ende - Willybrordus Lanamana (AGRICA, 2023)
The purpose of this study was to analyze the performance effectiveness of the local variety of Nuabosi cassava farmer groups in Randotonda Village. The research was conducted in Randotonda Village from April to June 2022. The population was 210 people. Determination of respondents with the purposive sampling method. The total number of respondents is 102 people. Data analysis; coding and grouping data, designing cross tables, and checking data. The influence between variables using multiple regression analysis. Test the validity and reliability of the instrument. The results showed that in the group leadership aspects of cohesiveness and meeting intensity, most of the respondents answered that they were in a low category. All aspects of group work variables are in medium and low ratings. Aspects of factors outside the group of high formal and non-formal leader support. Productivity and member satisfaction aspects are in a low category. There is an influence between characteristic group variables and group work variables partially on the level of group effectiveness. Out-of-group variables have no effect on group effectiveness level variables.